1996
DOI: 10.1111/j.1365-2044.1996.tb07897.x
|View full text |Cite
|
Sign up to set email alerts
|

Midazolam co‐induction and laryngeal mask insertion

Abstract: Summary We have studied the effect of alfentanil and midazolam + alfentanil on the conditions for laryngeal mask airway insertion in patients receiving propofol for induction of anaesthesia. Ninety unpremedicated, ASA 1 or 2 adult patients were randomly allocated to one of three groups: group P received propofol only (2.5 mg.kg‐1); group PA received alfentanil (10 μg.kg‐1) followed by propofol (1.25 mg.kg‐1); group PMA received midazolam (0.04 mg.kg‐1) and alfentanil (10 μg.kg‐1) followed by propofol (1.25 mg.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 13 publications
3
44
0
Order By: Relevance
“…In the present study, the undesirable responses-coughing, gagging, laryngospasm, desaturation were nil in both the groups, both at insertion and removal of LMA and findings concur with Driver IK et al 15 Table 5: Showing changes in mean heart rate and mean systolic blood pressure …”
Section: Discussion: Allsop E Et Alsupporting
confidence: 91%
See 3 more Smart Citations
“…In the present study, the undesirable responses-coughing, gagging, laryngospasm, desaturation were nil in both the groups, both at insertion and removal of LMA and findings concur with Driver IK et al 15 Table 5: Showing changes in mean heart rate and mean systolic blood pressure …”
Section: Discussion: Allsop E Et Alsupporting
confidence: 91%
“…They reported that the combination of propofol with midazolam or ketamine improved conditions for laryngeal mask insertion and produced stable haemodynamics. Similarly, in adults, Driver IK et al, 15 , Short TG et al 1 also reported that the propofol-midazolam combination acts synergistically. Thus, in the present study, propofol 3.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…Moreover, after 3 h and 6 h the AG performance was still slower, though not less accurate, than the CG performance. Propofol, fentanyl, and midazolam suppress the laryngeal and pharyngeal responses, which are crucial to vocalisation [19][20][21]. However, the pharmacokinetic properties of a hypnotic agent seem to exclude such a possibility -propofol disappears from the effectory compartment after several minutes and its metabolites are inactive.…”
Section: Discussionmentioning
confidence: 99%